Edukasi Pencegahan Penyalahgunaan Narkoba Melalui Penguatan Karakter Siswa SMA Negeri 1 Kota Bengkulu - Fepy Supriani; Rena Misliniyati; Lindung Zalbuin Mase; Hendri Hestiawan (Dharmakayana, 2026)
Drug abuse among adolescents is a critical issue that negatively affects their learning concentration, productivity, decision-making abilities, social behavior, and overall physical and mental well-being, while also increasing the risk of criminal behavior. Adequate knowledge about drugs is positively associated with adolescents’ ability to prevent drug misuse. This community service program aimed to enhance students’ knowledge and strengthen their character in preventing drug abuse through educational and interactive activities. The program targeted the eleventh-grade students of SMA Negeri 1 Kota Bengkulu, particularly class XI IPS 1. The methods applied included interactive workshops, presentations, small-group discussions, modeling, and role-playing. The activity was conducted on October 9, 2025, and was met with high enthusiasm and active participation from 30 students. Evaluation was carried out using pre-test and post-test assessments to measure changes in understanding. The results showed a significant improvement of 87% in post-test scores compared to pre-test scores, indicating an increase in students’ knowledge and capacity to recognize and prevent drug abuse. In addition to benefiting the participants, this program also helped enhance the brand image of the Faculty of Engineering, University of Bengkulu, among stakeholders. Overall, the character-based educational approach proved effective in raising awareness and understanding of drug-abuse prevention among adolescents business potential.